1318 Peri and Post-operative Fluid Management in Relation to Outcomes in Free Flap Reconstructive Surgery - A Systematic Review. (12th October 2021) - Shah, K S V; Fernando, S; Preena, D; Jigajinni, S; Ahmed, A
Abstract: Aim: Free tissue transfer is one of the options available in the armamentarium of the reconstructive surgeon. Being a highly demanding and skilled procedure, success is dependent not only on the technical aspect of the anastomosis, but also on other variables including a patient's fluid status. In order to address the controversy surrounding optimal fluid balance in free flap reconstruction, a systematic review of studies investigating the influence of peri and post- operative fluid balance on free flap reconstruction outcomes was carried out. Method: We searched the Medline database from 1970 to 2020 and manually searched the bibliographies of relevant studies. The articles were graded according to the level of evidence set out by the Centre for Evidenced-Based Medicine and followed the PRISMA guidelines. Results: Of the 62 abstracts screened, we identified 14 studies that met the inclusion criteria. Of the 14 studies, 12 studies concluded that excessive fluid therapy led to either medical or surgical complications (including free flap complications) or increased length of hospital stay. One study concluded that restricted fluid therapy led to a higher complication rate of delayed thrombotic events. One study reported no difference between volume of fluid administered with respect to pulmonary complications. Conclusions: An important aspect of successful microvascular reconstruction involves determining a patient's fluid status and targeted optimal resuscitation. This is best achieved with goal directed fluid therapy using tools such as an oesophageal doppler or other arterial waveform- based systems. Further good quality trials are required to determine which system is superior.